F-derivations on residuated multilattices - Celestin Lele; Line Nzoda Maffeu; Etienne Alomo Temgoua; Stefan Schmidt (Journal of Hyperstructures)
In this paper, we introduce as a generalization of the concept of derivation, the notion of f-derivation on residuated multilattices and investigate several of its properties. Then, we study good ideal f-derivations and make the connection with the complemented elements. Moreover, special sub-classes like the set of f-fixed points, the Kernel are found to have nice substructures.